Diterpene synthases facilitating production of the kaurane skeleton of eriocalyxin B in the medicinal plant Isodon eriocalyx. (February 2019) - Du, Gang; Gong, Hai-Yan; Feng, Ke-Na; Chen, Qian-Qian; Yang, Yan-Long; Fu, Xiao-Li; Lu, Shan; Zeng, Ying
Abstract: The Isodon plants (Lamiaceae) have been used in traditional Chinese medicine to alleviate sufferings from inflammations and cancers. This feature has been attributed to the presence of pharmacologically active ent -kaurane diterpenoids such as eriocalyxin B and oridonin. The Isodon eriocalyx (Dunn) Kudô species native to southwest China can accumulate a particularly high content of ent -kaurane diterpenoids (∼1.5% w/w of dried leaves). We previously identified diterpene synthases IeCPS1 and IeCPS2 as ent -copalyl diphosphate synthases ( ent -CPS) potentially involved in Isodon ent -kaurane diterpenoids biosynthesis. In this study, analysis of RNA-seq transcriptome of the I. eriocalyx plant revealed three other diterpene synthase genes ( IeCPS3, IeKS1, and IeKSL1 ). Their functional characterization through coupled in vitro enzyme assays has confirmed that IeCPS3 is an ent -CPS specifically producing ent -copalyl diphosphate ( ent -CPP). IeKS1 accepted ent -CPP to produce exclusively ent -kaurene and may thus be defined as an ent -kaurene synthase ( ent -KS). When IeKSL1 was combined with IeCPS2 or IeCPS3, no product was detected. Based on tissue-specific expression and metabolic localization studies, the IeCPS3 and IeKS1 transcripts were significantly accumulated in leaves where the ent -kaurane diterpenoid eriocalyxin B dominates, whereas weak expression of both were observed in germinating seeds in which gibberellin biosynthetic pathway is normally active. Our findings suggest that both IeCPS3 and IeKS1 possess dual roles in general (gibberellins) and specialized diterpenoid metabolism, such as that of the Isodon ent -kaurane diterpenoids. Graphical abstract: Highlights: Diterpene synthases IeCPS3, IeKS1 and IeKSL1 were identified in Isodon eriocalyx. IeCPS3 is an ent -copalyl diphosphate synthase; IeKS1 is an ent -kaurene synthase. IeCPS3 and IeKS1 are more abundant in leaves where eriocalyxin B accumulates. IeKSL1 is unable to produce ent -kaurene, and quite distinct from IeKS1.